Curcumin/Gd Loaded Apoferritin: A Novel "Theranostic" Agent To Prevent Hepatocellular Damage in Toxic Induced Acute Hepatitis - Cutrin, Juan Carlos (2013)
Apoferritin has been exploited to deliver simultaneously therapeutic and imaging agents (loaded into its internal cavity) to hepatocytes as this protein is efficiently taken up from blood by hepatocyte scavenger receptor class A type 5 via the ferritin transporting route. To this purpose the protein has been loaded with the magnetic resonance imaging (MRI) contrast agent GdHPDO3A and curcumin, a polyphenolic substance endowed with multiple pharmacological actions, namely: antioxidant, anti-inflammatory, antineoplastic. Curcumin and GdHPDO3A loaded apoferritin has been used with the aim to attenuate the thioacetamide-induced hepatitis together with the evaluation by MRI of drug delivery efficiency. Mice pretreated by intraperitoneal administration showed significantly attenuated hepatic injury as assessed by measuring alanine aminotransferase (ALT) activity in plasma and by histology assessment. The encapsulation of curcumin inside the apoferritin cavity significantly increases its stability and bioavailability while maintaining its therapeutic anti-inflammatory properties.